(untitled) (Baghdad Science Journal, 2025)
A study of Zooplankton community has been carried out at four selected sites on Dukan Lake. Samples of water and zooplankton were collected monthly for the period from July 2015 to February 2016. Some physical and chemical properties of water were studied and the results showed that the air temperature were ranged from 0 to 36.16 °C, water temperature ranged from 2.83 to 34.66 °C, hydrogen ion concentration of studied sites were found to lie in alkaline side, it was ranged between 6.87 to 8.57, electrical conductivity ranged from 190.79 to 850.08 µs.cm¹, turbidity ranged from 0.9-7.7 NTU, and dissolved oxygen from 3.3 to 6.8 mg.l-¹ while BOD5 were ranged from 0.53 to 34.66 mg.l-¹. Concerning to the zooplankton, 37 species were identified which belonged to Cladocera (48.38%), Copepod (43.28%), Rotifera (8.23%), Targigrada (0.08%) and Cnidaria (0.1%). The medusa of Craspedacusta sowerbii Lankester (1880) was recorded for the first time in Iraq. Regarding to zooplankton community, rotifer were ranged between 0 to 690.91 ind.m-3, Copepoda from 54.55 to 5927.27 ind.m-3 and Cladocera ranged from 18.18 to 6072.73 ind.m-3. According to Shanon-Weiner index, species diversity for zooplankton invertebrates was ranged from 0.325 to 1.091 bits/ind. Jaccard’s similarity index showed that the highest similarity was recorded between site (1) and site (4) with 40.74%.